Technikos ir žemės ūkio personalinė bibliografija Lietuvoje - Matulaitytė, Stasė (Knygotyra, 2024)
Investigating the development of a certain branch of science and the contribution of every scientist to the field is of great importance. A personal bibliographic index summarizing the results of a scientist’s work could be helpful. In Lithuania, various types of personal indices are compiled and issued. First of all, separate issues of exhaustive indices, including all the works of a scientist and literature about him/her, could be mentioned. Usually, they are compiled by bibliographers. Another group consists of indices published in books about scientists (e.g., Andrius Novodvorskis, Viktoras Ruokis, Jonas Kriščiūnas). They are usually compiled as well by bibliographers and cover all the works of a certain scientist and literature about him. The third group presents literature lists which are located at the end of an article (most often devoted to an anniversary) about a scientist. The lists are compiled by the authors of articles—colleagues of scientists. Therefore, the literature lists are non-standard, and only the main works of a scientist are named. Publications about the person are sometimes included as well. The above-mentioned lists only reflect the highlights of the activities of a person and do not suggest the comprehensive picture of the works accomplished. Another group of personal indices refers to the bibliographies compiled by various institutions or private persons (not bibliographers) to celebrate the anniversary of their colleague. This type of indices has just recently become fashionable. However, either personal indices’ compilation methods or publications’ bibliographical regulations are ignored in this type. The article presents a review of all the mentioned groups of personal indices of scientists in the fields of technology and agriculture, beginning with the first lists of these subjects up to the year 1996.